Composite solid electrolyte membrane and preparation method and application thereof

By constructing a composite solid electrolyte membrane, using in situ polymerization technology of inorganic electrolytes and polymers, the low conductivity and interface incompatibility of a single solid electrolyte membrane are solved, and a high-performance and long-life lithium battery is achieved.

CN119725690APending Publication Date: 2025-03-28SHANDONG HAIHUA CO LTD +1
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202411528039.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing single solid electrolyte membrane has problems such as low ionic conductivity, poor interfacial compatibility and large interfacial resistance, which cannot meet the needs of high-voltage positive electrodes and long-life lithium batteries.

Method used

Using an inorganic electrolyte as the substrate, a three-dimensional porous ceramic membrane is formed by removing the carbon skeleton, and a polymer solution is injected into it through in situ polymerization to construct a composite solid electrolyte membrane.

Benefits of technology

It achieves high ionic conductivity, excellent mechanical flexibility, good interface compatibility and high-voltage decomposition ability, which significantly improves the performance and life of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725690A_ABST
    Figure CN119725690A_ABST
Patent Text Reader

Abstract

The invention provides a composite solid-state electrolyte membrane and a preparation method and application thereof, and belongs to the field of lithium battery solid-state electrolytes.The preparation method comprises the steps that solid-state electrolyte powder and carbon precursor powder are pressed into a membrane and then subjected to gradient heating calcination, and a three-dimensional framework porous ceramic membrane is obtained; uniformly mixing a lithium salt, a polymer monomer and an initiator to prepare a polymerization solution; and dropwise adding the polymerization solution onto the three-dimensional skeleton porous ceramic membrane, and carrying out thermal polymerization to obtain the composite solid electrolyte membrane. Aiming at the inorganic solid electrolyte, the composite solid electrolyte membrane with high ionic conductivity and good interfacial compatibility is obtained in a mode of in-situ construction of the composite solid electrolyte membrane, and the problems that the inorganic solid electrolyte is low in ionic conductivity, poor in interface contact and not resistant to high pressure are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery solid electrolytes, and in particular to a composite solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] Compared with traditional lead-acid batteries, lithium batteries have the advantages of high energy density, long service life, and no memory effect. They have been widely used in electric vehicles, portable electronic devices, and large-scale power grid energy storage. Traditional liquid lithium batteries have low energy density and are prone to combustion and explosion when they are hit by collisions and punctures. Solid-state lithium batteries that use solid electrolytes instead of diaphragms and flammable organic electrolytes have the advantages of good thermal stability, high energy density, and high safety, and have become an important development direction for the next generation of lithium batteries.

[0003] At present, single solid electrolyte membranes have low ion conductivity, are prone to oxidative decomposition when matched with high-voltage positive electrodes, have poor interface compatibility with electrodes, and have large interface resistance, which cannot meet the needs of practical applications. In view of the above problems, the development of composite solid electrolytes with high ion conductivity, good stability and interface compatibility is the key to the development of solid-state batteries.

[0004] Inorganic / polymer composite electrolyte membranes can effectively combine the characteristics of inorganic solid electrolytes and polymer solid electrolytes, achieving "rigidity and flexibility" and ensuring good interface contact. The traditional sandwich structure (organic-inorganic-organic) composite solid electrolyte still has a large interface resistance and cannot improve the ionic conductivity inside the inorganic solid electrolyte. At the same time, the thickness of the composite solid electrolyte of this structure is large, which will greatly reduce the overall volume energy density of the lithium battery. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a composite solid electrolyte membrane, which uses an inorganic electrolyte as a substrate, obtains a three-dimensional porous inorganic electrolyte framework by removing the carbon skeleton, and injects a polymer solution into the inorganic electrolyte framework for in-situ polymerization to obtain a composite solid electrolyte membrane with excellent mechanical flexibility, high ionic conductivity, excellent interface compatibility and resistance to high-pressure decomposition.

[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) Grinding and mixing solid electrolyte powder and carbon precursor powder to obtain a mixed material; (2) Transferring the mixed material into a mold and pressing it into an electrolyte membrane; (3) calcining the obtained electrolyte membrane at high temperature to remove carbon and obtain a three-dimensional skeleton porous ceramic membrane; (4) uniformly mixing the lithium salt, polymer monomer and initiator in a certain proportion to obtain a polymer solution; (5) The polymer solution is dropped onto the three-dimensional porous ceramic membrane, and a composite solid electrolyte membrane is obtained after thermal polymerization.

[0007] In the step (1), the solid electrolyte powder is one of LLZO, LLTO, LATP and LAGP; the carbon precursor powder is one of PEO, PAN, PVDF, PMMA and chitosan; the mass ratio of the solid electrolyte powder to the carbon precursor powder is 10-30:1; and the grinding time is 0.5h. The ratio of the solid electrolyte powder to the carbon precursor powder is used to control the porosity of the three-dimensional porous ceramic membrane. The inventors found that when the mass ratio is less than 10:1, the porosity is too high and the mechanical strength of the composite solid electrolyte membrane is too low. When the mass ratio is greater than 30:1, the porosity is too low, the composite solid electrolyte membrane has low flexibility and poor interface compatibility.

[0008] In the step (2), the pressing pressure is 250-300 MPa.

[0009] In the step (3), the electrolyte membrane is calcined in a two-stage gradient heating method, the temperature of the gradient heating stage 1 is 300-500°C, the heating rate is 3-5°C / min, and the calcination time is 2-4h, and the temperature of the calcination stage 2 is 800-1000°C, the heating rate is 2-5°C / min, and the calcination time is 6-10h. The inventors found that the one-step calcination method leads to rapid growth and uneven growth of grains, insufficient reaction, formation of coarse grains, and even cracks, which affect the compactness of the solid electrolyte; secondly, it will also cause volatile substances and impurities to be unable to be fully decomposed and removed, forming more defects or pores, affecting the ion transmission performance of the material.

[0010] In the step (4), the lithium salt is one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalate borate; the polymer monomer is one of 1,3-dioxolane, ethylene glycol methyl ether acrylate, vinyl carbonate, ethylene carbonate, tetraethylene glycol diacrylate, and polyethylene glycol diacrylate; the initiator is one of azobisisobutyronitrile, aluminum trifluoromethanesulfonate, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; the mass ratio of the polymer monomer to the lithium salt is 1-3:1, and the mass of the initiator is 1%-5% of the mass of the polymer monomer; the stirring time is 3-5 hours, and the stirring speed is 600-800 r / min.

[0011] In the step (5), the mass ratio of the amount of the polymer solution added to the three-dimensional skeleton porous ceramic membrane is 1:1-5; the polymerization method is thermal polymerization, the polymerization temperature is 50-70°C, and the polymerization time is 4-6h.

[0012] The present invention also provides a composite solid electrolyte membrane prepared by the method.

[0013] The present invention also provides the use of the composite solid electrolyte membrane prepared by the above preparation method in a solid-state lithium battery.

[0014] The beneficial effects of the present invention are: Compared with the prior art, the beneficial effects of the present invention include at least: (1) The present invention uses an inorganic solid electrolyte to prepare a three-dimensional skeleton porous ceramic membrane, and injects a polymer electrolyte into the interior and surface of the three-dimensional skeleton porous membrane by in-situ polymerization. The electrolyte prepared by this method has a three-dimensional network interconnected structure inside, which provides a channel for the transmission of lithium ions, can effectively improve the transmission efficiency of lithium ions inside the electrolyte, and reduce the diffusion barrier of lithium ions. The ionic conductivity of the constructed composite solid electrolyte membrane can reach 2.94-4.25×10 -4 S / cm. (2) The surface of the composite solid electrolyte membrane constructed in situ by the present invention is a polymer, which can increase the compatibility with the negative electrode lithium interface and reduce the interface transmission resistance; at the same time, it effectively isolates the direct contact between the inorganic electrolyte and the lithium negative electrode, avoiding the metal lithium negative electrode from reducing the high-valent metal ions in the electrolyte and causing the decomposition of the solid electrolyte, thereby improving the cycle life of the battery. The symmetrical battery prepared by the composite solid electrolyte has a cycle life of 0.5 mA cm -2 , 0.5mAh cm -2 Under the condition of , the cycle life can reach 2860-4000h; at 1mAcm -2 , 1mAh cm -2 Under the condition of , the cycle life can reach 1300-2000h. (3) The flexible interface of the composite solid electrolyte membrane constructed by the present invention can increase the contact area between the electrolyte and the positive electrode, converting point-to-point contact to point-to-surface contact, effectively reducing the interface impedance. The full battery prepared using the composite solid electrolyte membrane can have a cycle life of 420-500 times at a current density of 1C. At the same time, the preparation method is simple and suitable for large-scale production of composite solid electrolyte membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Scanning electron microscope (SEM) photo of the composite solid electrolyte membrane prepared in Example 1 Figure 2 EIS diagram of a steel sheet-to-steel sheet battery assembled with the composite solid electrolyte membrane prepared in Example 1 as the electrolyte Figure 3Long cycle diagram of lithium-on-lithium symmetric battery assembled with the composite solid electrolyte membrane prepared in Example 1 Figure 4 Long cycle diagram of a full battery assembled with the composite solid electrolyte membrane prepared in Example 1 DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Examples of the embodiments are shown in the accompanying drawings. It should be understood that the specific embodiments described in the following embodiments of the present invention are only exemplary descriptions of the specific embodiments of the present invention, and are intended to be used to explain the present invention, but do not constitute a limitation of the present invention.

[0017] The endpoints of ranges and any values ​​disclosed herein are not limited to the exact range or value, and these ranges or values ​​should be understood to include approximations to these ranges. Example 1

[0018] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) LATP (Li 1+x Al x Ti 2-x (PO4)3, lithium aluminum titanium phosphate) solid electrolyte powder and PVDF (polyvinylidene fluoride) powder were ground for 0.5h and fully mixed at a mass ratio of 20:1 to obtain a mixed material; (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm, and the composite was pressed into a film at a pressure of 260 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 300°C for 3 h with a heating rate of 4°C / min, and then heated to 900°C at a heating rate of 4°C / min for 8 h. During this process, carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane. (4) vinylene carbonate and lithium tetrafluoroborate were mixed in a mass ratio of 3:1, and 3% of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added as an initiator and stirred at 750 r / min for 4 h to obtain a uniform polymer solution; (5) The polymer solution was added dropwise onto the three-dimensional skeleton porous ceramic membrane, with the mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane being 1:3. The membrane was placed in an oven at 60°C for 4 h for heating in situ polymerization to obtain a composite solid electrolyte membrane. Example 2

[0019] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) grinding LATP solid electrolyte powder and PMMA (polymethyl methacrylate) powder at a mass ratio of 15:1 for 0.5 h to fully mix and obtain a mixed material; (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm, and the composite was pressed into a film at a pressure of 270 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 300°C for 2.5h with a heating rate of 3°C / min, and then heated to 850°C at a heating rate of 3°C / min for 7h. During this process, carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane; (4) 1,3-dioxolane and lithium bis(trifluoromethanesulfonyl)imide were mixed in a mass ratio of 1:1, and 2% aluminum trifluoromethanesulfonate was added as an initiator and stirred at 750 r / min for 3.5 h to obtain a uniform polymer solution; (5) The polymer solution was dropped onto the ceramic membrane with a three-dimensional framework. The mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane was 1:2. The mixture was placed in an oven at 55°C for 5 h for heating in situ polymerization to obtain a composite solid electrolyte membrane. Example 3

[0020] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) LAGP (Li 1+x Al x Ge 2-x (PO4)3, lithium germanium aluminum phosphate) solid electrolyte powder and PAN (polyacrylonitrile) powder were ground for 0.5h and fully mixed at a mass ratio of 10:1 to obtain a mixed material; (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm and pressed into an electrolyte membrane at a pressure of 250 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 300°C for 2 h with a heating rate of 3°C / min, and then heated to 800°C at a heating rate of 2°C / min for 6 h. During this process, the carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane; (4) Ethylene glycol methyl ether acrylate and lithium difluorooxalate borate were mixed in a mass ratio of 3:1, and 1% aluminum trifluoromethanesulfonate was added as an initiator and stirred at 800 r / min for 3 h to obtain a uniform polymer solution; (5) The polymer solution was dropped onto the three-dimensional skeleton porous ceramic membrane, and the mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane was 1:1. The membrane was placed in an oven at 50°C for 6 hours for heating in situ polymerization to obtain a composite solid electrolyte membrane. Example 4

[0021] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) LLTO (Li 3x La 2 / 3x TiO3, lithium lanthanum zirconium oxide (LTZO) solid electrolyte powder and PEO (polyethylene oxide) powder were ground for 0.5 h and fully mixed at a mass ratio of 10:1 to obtain a mixed material. (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm, and the composite was pressed into a film at a pressure of 280 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 400°C for 3.5 h with a heating rate of 5°C / min, and then heated to 950°C at a heating rate of 4°C / min for 9 h. During this process, carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane. (4) Ethylene carbonate and lithium bis(fluorosulfonyl)imide were mixed in a mass ratio of 2:1, and 4% azobisisobutyronitrile was added as an initiator and stirred at 700 r / min for 4.5 h to obtain a uniform polymer solution; (5) The polymer solution was added dropwise onto the three-dimensional skeleton porous ceramic membrane, the mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane was 1:4, and the membrane was placed in an oven at 65°C for 4.5 hours for heating in situ polymerization to obtain a composite solid electrolyte membrane. Example 5

[0022] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) LLZO (Li7La3Zr2O 12 , lithium lanthanum zirconium oxide (LZO) solid electrolyte powder and chitosan powder are ground for 0.5 h at a mass ratio of 30:1 and 10:1 at a mass ratio to obtain a mixed material; (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm, and the composite was pressed into a film at a pressure of 300 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 500°C for 4 h with a heating rate of 5°C / min, and then heated to 1000°C at a heating rate of 5°C / min for 10 h. During this process, carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane. (4) Polyethylene glycol diacrylate and lithium hexafluorophosphate were mixed in a mass ratio of 1:1, and 5% azobisisobutyronitrile was added as an initiator and stirred at 600 r / min for 5 h to obtain a uniform polymer solution; (5) The polymer solution was dripped onto the three-dimensional skeleton porous ceramic membrane, and the mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane was 1:5. The membrane was placed in an oven at 70°C for 4 hours for heating in situ polymerization to obtain a composite solid electrolyte membrane. Example 6

[0023] A method for preparing a composite solid electrolyte membrane comprises the following steps: (1) grinding LATP solid electrolyte powder and PMMA (polymethyl methacrylate) powder at a mass ratio of 15:1 for 0.5 h to fully mix and obtain a mixed material; (2) 800 mg of the mixed material was placed in a mold with a diameter of 18 mm, and the composite was pressed into a film at a pressure of 270 MPa; (3) The obtained electrolyte membrane was first pre-calcined at 300°C for 2.5h with a heating rate of 3°C / min, and then heated to 850°C at a heating rate of 3°C / min for 7h. During this process, carbon was completely removed to obtain a three-dimensional skeleton porous ceramic membrane; (4) Tetraethylene glycol diacrylate and lithium bis(trifluoromethanesulfonyl imide) were mixed in a mass ratio of 2:1, and 2% aluminum trifluoromethanesulfonate was added as an initiator and stirred at 700 r / min for 3.5 h to obtain a uniform polymer solution; (5) The polymer solution was dropped onto the ceramic membrane with a three-dimensional framework, and the mass ratio of the polymer solution to the three-dimensional skeleton porous ceramic membrane was 1:2. The mixture was placed in an oven at 60°C for 5 h for heating in situ polymerization to obtain a composite solid electrolyte membrane. Comparative Example 1 (Preparation of a three-dimensional porous ceramic membrane with low porosity)

[0024] In this comparative example, when preparing the three-dimensional skeleton porous ceramic membrane, the ratio of solid electrolyte powder to carbon precursor powder is 40:1, and the other preparation steps and process parameters are consistent with those of Example 1. Comparative Example 2 (Preparation of three-dimensional porous ceramic membranes using different calcination methods)

[0025] In this comparative example, a one-step calcination method is used to prepare the three-dimensional skeleton porous ceramic membrane, directly raising the temperature to 900° C. and keeping the temperature for 8 hours. The other preparation steps and process parameters are consistent with those of Example 1. Comparative Example 3 (Preparation of a composite solid electrolyte membrane with a sandwich structure)

[0026] This comparative example prepares a composite solid electrolyte membrane with a "sandwich" structure, comprising the following steps: (1) Pressing LATP solid electrolyte powder into ceramic sheets at a pressure of 250 MPa; (2) The ceramic sheet was first pre-calcined at 300 °C for 2 h with a heating rate of 3 °C / min, and then heated to 800 °C at a heating rate of 2 °C / min for 6 h; (3) 1,3-Dioxolane and lithium bis(trifluoromethanesulfonyl imide) were mixed in a mass ratio of 3:1, and 1% aluminum trifluoromethanesulfonate was added as an initiator. The mixture was stirred at 800 r / min for 6 h to obtain a uniform polymer solution. The polymer solution was poured into a mold, dried in an oven at 50°C, and cut into electrolyte membranes of the same size as the ceramic sheet.

[0027] (4) The obtained electrolyte membrane is placed on both sides of the ceramic sheet to assemble into a composite solid electrolyte membrane with a sandwich structure. Application Examples

[0028] The composite solid electrolyte membranes prepared in Examples 1-5 and Comparative Examples 1-3 were assembled into symmetrical batteries for impedance testing and ionic conductivity calculation. The composite solid electrolyte membranes were made of stainless steel sheets on both sides, and the assembled battery model was a 2032 button battery. The electrochemical impedance spectroscopy test was performed, and the impedance value of the semicircular arc was obtained by fitting the equivalent circuit diagram. The value of the intersection was substituted into the formula σ=L / RS (L is the thickness of the composite solid electrolyte membrane, S is the electrode area, and R is the resistance value obtained by fitting), and the ionic conductivity was calculated by the formula.

[0029] The composite solid electrolyte membranes prepared in Examples 1-5 and Comparative Examples 1-3 were assembled into symmetrical cells and full cells. In the symmetrical cells, the lithium sheet was used as the working electrode, and the composite solid electrolyte membrane was used as both a diaphragm and an electrolyte. They were assembled into 2032-type button cells for electrochemical performance testing. When assembling the full cell, the positive electrode sheet active material was lithium iron phosphate, and the mass ratio of lithium iron phosphate, conductive carbon black, and polyvinylidene fluoride was 8:1:1. N-methylpyrrolidone was used as the solvent, and the ratio of the solvent to the lithium iron phosphate active material was 1.5:1. The above materials were mixed and ground into a slurry, which was coated on an aluminum foil with a coating thickness of 200 μm. The slurry was vacuum dried at 80°C for 12 h, and compacted to obtain a lithium-ion battery positive electrode sheet. The lithium sheet was used as the negative electrode, and the composite solid electrolyte membrane was used as the electrolyte. The slurry was assembled into a 2032-type button cell for cycle performance testing.

[0030]

[0031] Figure 1 The surface morphology SEM photo of the composite solid electrolyte membrane prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the composite solid electrolyte membrane is flat and dense, which is conducive to the rapid transmission of ions inside the electrolyte.

[0032] The composite solid electrolyte membrane prepared in Example 1 was used to assemble a symmetrical battery with stainless steel sheets on both sides to perform an electrochemical impedance spectroscopy test. Figure 2As shown, the ionic conductivity of the composite solid electrolyte membrane can be obtained by calculation (Table 1). The results show that the ionic conductivity of the composite solid electrolyte membrane prepared in Example 1 is 3.66×10 -4 S cm -1 , confirming that the composite solid electrolyte membrane prepared by the present invention has a high ionic conductivity. The composite solid electrolyte membrane prepared in Example 1 is used to assemble a symmetrical battery with lithium on both sides. Figure 3 The assembled symmetric cell was charged at a current density of 0.5 mA cm -2 , with a capacity of 0.5 mAh cm -2 The results show that under this test condition, the cycle life of the symmetrical battery can reach 4000h, indicating that the interface compatibility between the solid electrolyte membrane and the negative electrode lithium is good. It also shows that the preparation of the composite solid electrolyte membrane can effectively solve the problem of solid electrolyte decomposition caused by direct contact between the inorganic electrolyte and the lithium negative electrode. The composite solid electrolyte membrane prepared in Example 1 is used to assemble a full battery. Figure 4 The long cycle diagram of the assembled full battery. The results show that at 1C (170mA g -1 ) current density, 500 cycles of stable cycling can be achieved, and the specific capacity can be as high as 152 mAh g -1 , the capacity retention rate is close to 100%, indicating that the construction of the composite solid electrolyte membrane significantly increases the contact area between the electrolyte and the positive electrode and effectively reduces the interface impedance.

[0033] The composite solid electrolyte membranes prepared in Examples 2-6 were tested in the same manner as in Example 1, and the results were similar to those in Example 1 (Table 1). The ionic conductivity of the composite solid electrolyte membranes was 2.94-4.25×10 -4 S / cm, the prepared symmetric battery is at 0.5 mA cm -2 , 0.5mAh cm -2 Under the condition of , the cycle life can reach 2860-4000h; at 1mAcm -2 , 1mAh cm -2 Under the conditions, the cycle life can reach 1300-2000h; the cycle life of the prepared full battery can reach 420-500 times at a current density of 1C.

[0034] The composite electrolyte membrane prepared in Comparative Example 1 has a lower porosity than that of Examples 1-6, and its ionic conductivity is significantly lower than that of the samples prepared in Examples 1-6. At the same time, the cycle life of the symmetrical battery and the full battery prepared with it as the electrolyte is also significantly lower than that of Examples 1-6. The life of the symmetrical battery is only 1100h (0.5mA cm -2 , 0.5mAh cm -2) and 850h (1 mA cm -2 , 1mAh cm -2 ), the cycle number of the full battery is only 185 cycles, indicating that too high or too low porosity is not conducive to the acquisition of high-performance electrocatalytic performance. Therefore, the preparation method of the present invention requires a mass ratio of solid electrolyte powder to carbon precursor powder of 10-30:1. In Comparative Example 2, compared with Examples 1-6, when preparing the composite solid electrolyte membrane, the calcination adopts a one-step calcination method, and the obtained three-dimensional skeleton porous ceramic membrane has poor crystallinity and reduced ionic conductivity. When the symmetric battery test is performed, its cycle life is only 920h (0.5mA cm -2 , 0.5mAh cm -2 ) and 680h (1mA cm -2 , 1mAh cm -2 ), the number of cycles of the full battery is only 163, indicating that the two-stage gradient temperature rise sintering method in the present invention is necessary, and the ionic conductivity and electrochemical performance of the sample can be improved by using this sintering method. In Comparative Example 3, relative to the in-situ polymerization strategy of Examples 1-6, a composite solid electrolyte membrane with a sandwich structure is prepared. This sandwich structure has a large interface resistance and cannot achieve high current density cycling. In the cycle test of the symmetrical battery and the full battery, the cycle life of the symmetrical battery is only 615h (0.5mA cm -2 , 0.5mAh cm -2 ) and 480h (1mA cm -2 , 1mAh cm -2 ), the cycle life of the whole battery is only 230 cycles, which is far less than the cycle life of the symmetrical battery assembled with the composite solid electrolyte membrane prepared by the preparation method of the present invention as the electrolyte. This shows that the method of in-situ construction of solid electrolyte of the present invention can improve interface compatibility, reduce interface transmission resistance, and enhance the transmission efficiency of carriers at the interface as well as the cycle life of the battery under high current.

[0035] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and do not constitute a limitation on the content of the present invention. Within the technical concept of the present invention, the technical solutions of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a composite solid electrolyte membrane, characterized in that: The following steps are involved: (1) Grinding and mixing the solid electrolyte powder and the carbon precursor powder to obtain a uniform mixed material; (2) Transferring the mixed material into a mold and pressing it into an electrolyte membrane; (3) calcining the obtained electrolyte membrane at high temperature to remove carbon and obtain a three-dimensional skeleton porous ceramic membrane; (4) uniformly mixing the lithium salt, polymer monomer and initiator to obtain a polymer solution; (5) The polymer solution is added dropwise onto the three-dimensional skeleton porous ceramic membrane, and a composite solid electrolyte membrane is obtained after thermal polymerization.

2. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the step (1), the solid electrolyte powder is one of LLZO, LLTO, LATP and LAGP; the carbon precursor powder is one of PEO, PAN, PVDF, PMMA and chitosan; the mass ratio of the solid electrolyte powder to the carbon precursor powder is 10-30:1; and the grinding time is 0.5h.

3. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: In the step (2), the pressing pressure is 250-300 MPa.

4. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the step (3), the electrolyte membrane is calcined in a two-stage gradient heating method, wherein the temperature of the gradient heating stage 1 is 300-500°C, the heating rate is 3-5°C / min, and the calcination time is 2-4h; the temperature of the calcination stage 2 is 800-1000°C, the heating rate is 2-5°C / min, and the calcination time is 6-10h.

5. The method for preparing the composite solid electrolyte membrane according to claim 1, characterized in that: In the step (4), the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorooxalate borate; the polymer monomer is one of 1,3-dioxolane, ethylene glycol methyl ether acrylate, vinyl carbonate, ethylene carbonate, tetraethylene glycol diacrylate, and polyethylene glycol diacrylate; the initiator is one of azobisisobutyronitrile, aluminum trifluoromethanesulfonate, and 2-hydroxy-2-methyl-1-phenyl-1-propanone; the mass ratio of the polymer monomer to the lithium salt is 1-3:1, the mass of the initiator is 1%-5% of the mass of the polymer monomer, the stirring time is 3-5 hours, and the stirring speed is 600-800 r / min.

6. The method for preparing a composite solid electrolyte membrane according to claim 1, characterized in that: In the step (5), the mass ratio of the amount of the polymer solution added to the three-dimensional skeleton porous ceramic membrane is 1:1-5; the polymerization temperature of the thermal polymerization is 50-70°C, and the polymerization time is 4-6h.

7. A composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The composite solid electrolyte membrane has a three-dimensional network interconnected structure inside, and the surface of the composite solid electrolyte membrane is a polymer.

8. An application of a composite solid electrolyte membrane prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The prepared composite solid electrolyte membrane is applied in solid-state lithium batteries.

Citation Information

Cited By

  • Composite electrolyte precursor and preparation method and application thereof

    CN120089798A

  • Solid-state lithium battery polymer electrolyte and preparation method thereof

    CN120545444A

  • Solid-state electrolyte membrane based on bicontinuous lithium conduction network and preparation method and application of solid-state electrolyte membrane

    CN120727943A

  • Solid-state electrolyte membrane based on bicontinuous lithium-conducting network and preparation method and application thereof

    CN120727943B

  • Intercalation type composite solid electrolyte as well as preparation method and application thereof

    CN121282325A